Changes in acute viral hepatitis epidemiology in the Turkish adult population: A multicenter study - Karacaer, Zehra; Tosun, Selma; Batırel, Ayşe; Şahin, Suzan; Altaş, İrem and Uysal, Serhat and Erol, Serpil and Ceran, Nurgül and Albayrak, Ayşe and Yıldız, İlknur Esen and et al. (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: The present study aimed to determine the changes in the epidemiology of hepatitis in recent years in an adult Turkish population. Materials and Methods: Overall, 852 patients with acute viral hepatitis from 17 centers were included in this study. Their sociodemographic characteristics, clinical courses, treatments, and laboratory findings were retrospectively analyzed. Results: The most commonly found microorganisms were the hepatitis B virus (55.2%) and hepatitis A virus (37.6%), and the types of acute viral hepatitis differed significantly according to the age group (p≤0.001). The most frequently reported symptom was fatigue (73.7%), and the most common complications were cholecystitis (0.4%) and fulminant hepatitis (0.4%). The median hospital stay was 9 days (range 1-373). In total, 40.8% patients with acute hepatitis B virus developed immunity. Conclusion: In Turkey, there are significantly large adolescent and adult populations susceptible to acute viral hepatitis. Therefore, larger vaccination programs covering these age groups should be implemented. Cite this article as: Karacaer Z, Tosun S, Batırel A, et al. Changes in acute viral hepatitis epidemiology in the Turkish adult population: A multicenter study. Turk J Gastroenterol 2018; 29: 177-82.